2010
DOI: 10.1094/pdis-94-9-1076
|View full text |Cite
|
Sign up to set email alerts
|

Mancozeb: Past, Present, and Future

Abstract: This feature article reviews the broad-spectrum fungicide mancozeb. Introduced in 1962, it still plays a significant role in the world fungicide market. Mancozeb possesses a number of key attributes that have contributed toward its development into a globally important tool in modern chemical-based plant disease management. These attributes are discussed from the perspective of both public and private research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
97
0
21

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(130 citation statements)
references
References 114 publications
3
97
0
21
Order By: Relevance
“…Similarly, Catão et al (2013) also reported this mixture to be effective against A. tomatopila Simmons. Mancozeb is often used in combination with other active ingredients as it has many sites of action, therefore delaying the occurrence of pathogen resistant strains (Gullino et al, 2010). Copper hydroxide and copper hydroxide-copper equivalent were the least effective compounds in controlling AB among all the fungicides tested during all the growing seasons and at all sites.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Catão et al (2013) also reported this mixture to be effective against A. tomatopila Simmons. Mancozeb is often used in combination with other active ingredients as it has many sites of action, therefore delaying the occurrence of pathogen resistant strains (Gullino et al, 2010). Copper hydroxide and copper hydroxide-copper equivalent were the least effective compounds in controlling AB among all the fungicides tested during all the growing seasons and at all sites.…”
Section: Discussionmentioning
confidence: 99%
“…This known for years protective fungicide has a quite effective protective treatment. However, it is not effective enough when plants are diseased stronger (Gullino et al 2010;Urban and Filipowicz 2004). In the conducted research its effectiveness was not too high regardless of used nozzles.…”
Section: Discussionmentioning
confidence: 99%
“…Mankozeb merupakan racun kontak yang menghambat perkecambahan spora berbagai kelas cendawan (Gullino et al 2010) dan efektif sebagai protektan atau sebelum terjadi infeksi (Wong dan Wilcox 2001). Setelah terjadi kontak dengan air, mankozeb melepas ethylen bisisothiocyanate sulfidae (EBIS), terurai lagi menjadi ethylen bisisothiocyanate (EBI) yang beracun dan merusak sistem enzim di dalam sitoplasma dan mitokondria sel cendawan (Gullino et al 2010).…”
Section: Pembahasanunclassified
“…Setelah terjadi kontak dengan air, mankozeb melepas ethylen bisisothiocyanate sulfidae (EBIS), terurai lagi menjadi ethylen bisisothiocyanate (EBI) yang beracun dan merusak sistem enzim di dalam sitoplasma dan mitokondria sel cendawan (Gullino et al 2010).…”
Section: Pembahasanunclassified